2015
DOI: 10.1016/j.carbon.2015.02.053
|View full text |Cite
|
Sign up to set email alerts
|

Double walled carbon nanotubes promote the overproduction of extracellular protein-like polymers in Nitzschia palea: An adhesive response for an adaptive issue

Abstract: A B S T R A C TThe present study assessed the effects of double-wall carbon nanotubes (DWCNTs) dispersed in the presence of a realistic concentration of natural organic matter (NOM, 10 mg L À1 ) on the benthic diatom Nitzschia palea using toxicity tests and quantitative/qualitative extracellular polymeric substances (EPS) assays. No toxic effect was observed. A growth delay was measured after 48 h of exposure to concentrations of DWCNTs ranging from 1 mg L À1 ($29%) to 50 mg L À1 ($84%). Extracellular carbohyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…Furthermore, the secretion of polysaccharides in the medium seems to be a defense mechanism of algae against heavy metals [35,72]. More recently, Verneuil et al [73] also demonstrated the role of EPS production in diatoms cultures exposed to CNTs. The authors reported the high proportion of hydrophobic proteins in EPS, which represent the primary part of extracted EPS.…”
Section: Investigation Of the Interaction Between Diatoms Biofilm Andmentioning
confidence: 97%
“…Furthermore, the secretion of polysaccharides in the medium seems to be a defense mechanism of algae against heavy metals [35,72]. More recently, Verneuil et al [73] also demonstrated the role of EPS production in diatoms cultures exposed to CNTs. The authors reported the high proportion of hydrophobic proteins in EPS, which represent the primary part of extracted EPS.…”
Section: Investigation Of the Interaction Between Diatoms Biofilm Andmentioning
confidence: 97%
“…[73] On doublewalled carbon nanotubes (DWNTs), 10 and 174 kDa protein-like polymers were identified as the predominant adsorbed components of EPS secreted by Nitzschia palea. [74] In terms of the binding strength with microbial cells, the EPS from algal aggregates may be fractionated into loosely bound EPS (LB-EPS) and tightly bound EPS (TB-EPS). [75] Spectral analysis has revealed that tryptophan and humic-like components in TB-EPS exhibit higher binding capacities to CuO NPs and Fe 3 O 4 NPs than those in LB-EPS.…”
Section: Extracellular Polymeric Substancesmentioning
confidence: 99%
“…These organisms are thus a critical group to look at for assessing the effects of CNPs on the environment. Effects of two different types of CNTs (double walled: DWCNTs and multiwalled: MWCNTs) were assessed on the benthic diatom Nitzschia palea [27,28]. Results showed that environmentally realistic concentrations of natural organic matter (NOM) used as a dispersant could increase the short term growth inhibition induced by CNTs.…”
Section: Release and Fatementioning
confidence: 99%
“…For instance, oxidized particles appear more toxic and are associated with oxidative stress. Some characteristics, such as the presence of the cellular wall or the secretion of EPS seem to make algae more resistant [27][28][29] compared to other organisms [30]. The question of the role of oxygen-containing functions is still debated because not only this modifies the surface chemistry on the CNPs and thus their surface charge depending on the pH, but it also contributes to make them much easier to disperse in water.…”
Section: Release and Fatementioning
confidence: 99%